2017
DOI: 10.4103/jisp.jisp_292_17
|View full text |Cite
|
Sign up to set email alerts
|

A clinicoradiographic assessment of 1% metformin gel with platelet-rich fibrin in the treatment of mandibular grade II furcation defects

Abstract: Background:Management of furcation defects is challenging, and constantly newer therapeutic strategies are evolving. Platelet-rich fibrin (PRF) is successfully used alone and in combination with various agents in the furcation defects. Lately, metformin (MF), a second generation biguanide has gained popularity owing to its osteogenic potential.Aims and Objectives:The aim of the present study was to evaluate the clinical and radiographic effectiveness of open flap debridement (OFD) and PRF when compared to OFD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 32 publications
6
7
1
2
Order By: Relevance
“…Greater attachment levels and bone-fill were notable findings. Similar improvements in patient outcomes were observed for mandibular Grade II furcation defects [74] and gingival recession defects [75,76,77,78,79,80,81]. Its ability to relieve pain and post-operative swelling during tooth extractions and in the treatment of tooth lesions, are also widely documented [82,83,84,85,86,87,88,89,90,91,92].…”
Section: Methods—literature Reviewmentioning
confidence: 61%
“…Greater attachment levels and bone-fill were notable findings. Similar improvements in patient outcomes were observed for mandibular Grade II furcation defects [74] and gingival recession defects [75,76,77,78,79,80,81]. Its ability to relieve pain and post-operative swelling during tooth extractions and in the treatment of tooth lesions, are also widely documented [82,83,84,85,86,87,88,89,90,91,92].…”
Section: Methods—literature Reviewmentioning
confidence: 61%
“…A similar study was performed Taneja et.al, comparing the differences between PRF/MFT and PRF at 6 and 9 months [82]. A study was also found evaluating the possible use of OFD/PRF/MFT in the treatment of grade II mandibular furcation defects [81]. It has been shown that biguanide drugs in combination with PRF is widely used in periodontal therapy, which indicates the ability of PRF to be a drug delivery vehicle.…”
Section: Biguanidesmentioning
confidence: 79%
“…Three studies evaluated the treatment outcomes of L-PRF besides OFD compared with OFD alone. 22,78,79 In four studies, L-PRF was applied mixed with other materials including metformin gel, 80 bioactive ceramic composite granules (BCCG), 81 rosuvastatin, 82 hydroxyapatite (HA), 82 and alendronate. 83 Asimuddin et al 84 compared the effect of PRF alone with allograft and healiguide collagen membrane.…”
Section: Management Of Furcation Defectsmentioning
confidence: 99%
“…Siddiqui et al 79 suggested that using β-tricalcium phosphate (β-TCP) lead to better treatment outcomes when compared with PRF. It was shown that when PRF applied mixed with rosuvastatin and HA, 82 alendronate, 83 and metformin, 80 the treatment outcome improved when compared with PRF alone. Furthermore, Lohi et al 81 reported that supplemental use of PRF besides BCCG led to significant improvements in all measured parameters.…”
Section: Management Of Furcation Defectsmentioning
confidence: 99%
See 1 more Smart Citation